CGIAR Agroecology Initiative Outcome Identification Workshop Makueni ALL - Korir, Hezekiah; Ngige, Chris; Adoyo, Beatrice; Anyango, Edith; Onyango, Kevin; Bolo, Peter; Gumo, Pius; Njeri, Rhoda; Fuchs, Lisa Elena (2024)
Since 2023, the Agroecology Initiative has engaged with diverse stakeholders in Makueni ALL to co-design and implement innovative agroecological practices in three priority areas: soil, water, and integrated pest management. To assess the Initiative's impact on various food system actors, an outcome evidence workshop was held on September 3, 2024, at DNRC, Makueni. This workshop involved 35 participants from diverse sectors, including farmers, government officials, and the private sector, agro-input service providers, NGOs, implementing organizations.